2001
DOI: 10.1006/bijl.2001.0542
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of animal dispersal, vicariance and diversification in the Holarctic

Abstract: We analysed patterns of animal dispersal, vicariance and diversification in the Holarctic based on complete phylogenies of 57 extant non-marine taxa, together comprising 770 species, documenting biogeographic events from the Late Mesozoic to the present. Four major areas, each corresponding to a historically persistent landmass, were used in the analyses: eastern Nearctic (EN), western Nearctic (WN), eastern Palaeoarctic (EP) and western Palaeoarctic (WP). Parsimony-based tree fitting showed that there is no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
149
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(166 citation statements)
references
References 36 publications
6
149
1
1
Order By: Relevance
“…Boloria (Simonsen et al, 2010), Limenitis (Mullen, 2006) or Coenonympha (Kodandaramaiah and Wahlberg, 2009). Oeneis butterflies dispersed to North America through the second (from the Miocene to the late Pliocene, 14-3.5 Ma) and the third (the Pleistocene, 1.5-1 Ma) Beringian Land Bridge (Sanmartin et al, 2001). After the submersion of the second Beringian Land Bridge, isolation likely led to the origin of subgenus Neominois and O. uhleri, and probably also to the split of sister pair O. chryxus and O. bore (Figs.…”
Section: Biogeographymentioning
confidence: 99%
“…Boloria (Simonsen et al, 2010), Limenitis (Mullen, 2006) or Coenonympha (Kodandaramaiah and Wahlberg, 2009). Oeneis butterflies dispersed to North America through the second (from the Miocene to the late Pliocene, 14-3.5 Ma) and the third (the Pleistocene, 1.5-1 Ma) Beringian Land Bridge (Sanmartin et al, 2001). After the submersion of the second Beringian Land Bridge, isolation likely led to the origin of subgenus Neominois and O. uhleri, and probably also to the split of sister pair O. chryxus and O. bore (Figs.…”
Section: Biogeographymentioning
confidence: 99%
“…Throughout this section, we refer to plate tectonic events and their timing as summarised in Sanmartín et al (2001), Sanmartín and Ronquist (2004) and Bossuyt et al (2006). Korn et al (2010) demonstrated that in gonochoric lineages of Notostraca, repeated short-distance dispersal is likely to be the prevailing mechanism during range extensions.…”
Section: Biogeographymentioning
confidence: 99%
“…50-55 Ma (see Sanmartín et al, 2001). Alternatively, the lineage of American endemics could have diverged during a range extension from Europe into Asia during a temporary regression of the Turgai Sea in the Palaeocene (see Sanmartín et al, 2001; the Palaeocene spans 56-66 Ma, see Cohen et al, 2012), followed by an additional eastward dispersal over Beringia to Eastern North America (the single record of a Lepidurus population from South America, that of L. apus patagonicus, might also refer to this lineage, however, presently available data are insufficient to confirm this assumption). The L. apus viridis lineage possibly evolved in Eastern Asia from where it could have reached Australia and New Zealand by long-distance dispersal, facilitated by its non-gonochoric mode of reproduction.…”
Section: Biogeography Of the Genus Lepidurusmentioning
confidence: 99%
“…In the early Cretaceous, the ancestors of the Esculenta and Elata Clades originated in western North America, and then spread to eastern North America. Due to the emergence of the Mid-Continental Seaway in the mid Cretaceous and the subsequent uplift of the Rocky Mountains during the late Cretaceous (Sanmartín et al 2001), significant obstacles to gene flow among the morels formed between western and eastern North America, leading to the divergence of the ancestors of the Esculenta and Elata Clades diverging into the Elata Clade and the Esculenta Clade in western and eastern North America, respectively, during the late Cretaceous. New species evolved in eastern and western North America independently, with little exchange between the two regions (such as M. americana M. Kuo, Dewsbury, Moncalvo & S.L.…”
Section: Evolutionary History Of Morchellamentioning
confidence: 99%
“…Most species crossed the Beringian Land Bridge and dispersed to Asia. In the late Oligocene, and continuing in the Miocene, new folding of the Rocky Mountains and uplift of the Sierra Madre Oriental Range caused cooler and drier climates in central North America (Sanmartín et al 2001; Donoghue and Smith 2004), which probably resulted in the widespread extinction of Morchella in that region.
10.1080/21501203.2015.1016561-F0002Figure 2.Hypothesis of place of origin, migration routes, and rapid radiation and speciation of morels.
…”
Section: Evolutionary History Of Morchellamentioning
confidence: 99%